Crisis económica internacional y las exportaciones de una economía pequeña: un análisis modelístico - León Mendoza, Juan (2011)
This article aims to analyze the effects generated by international economic crisis on the exports of a small open economy. Assuming that the international crisis is expressed in global recession and increases in the exchange rate, we evaluate the effect of these two facts on exports through graphical simulations of a previously developed microeconomic model. In the framework of the model of a global recession, especially of the most important countries, results in a fall in import demand, leading to a decline in international prices and, consequently, a decrease of exports. The drop in exports is higher in the non-traditional sector than the traditional exports. The increase in the exchange rate affects exports positively.